THU0124 Higher Methotrexate Dose May Increase the Frequency of Lymphoproliferative Disorders in Rheumatoid Arthritis Patients. (10th June 2014) - Dobashi, H.; Kameda, T.; Inoo, M.; Onihsi, I.; Kurata, N.; Mitsunaka, H.; Susaki, K.; Izumikawa, M.; Nakashima, S.; Shimada, H.; Takeuchi, Y.; Ozaki, H.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a systemic inflammatory disease that is characterized by synovitis and the destruction of articular structures of multiple joints. The goal of treatment for RA is to control the progression of these articular lesions. MTX is an antirheumatic drug that is expected to have an excellent suppressive effect on articular destruction. Recently, MTX has been used as an anchor drug for the treatment of RA (1). On the other hand, RA patients have a high risk of onset of lymphoproliferative disorders (LPD) (2). Although MTX-LPD occurs mainly in RA patients, it has not been established if MTX administration is an independent risk factor for LPD in RA patients. Objectives: We examined the clinical characteristics of MTX-LPD in Japanese RA patients and attempted to determine the risk factors for MTX-LPD development. Methods: We performed a nested case-control study on RA patients. We enrolled 5, 783 RA patients from Kagawa Prefecture, Japan between June 2003 and Dec 2013. Patients were diagnosed according to American College of Rheumatology 1987 classification criteria, and treated with disease modifying antirheumatic drugs (DMARDs) including MTX. In age and gender matched patients, we separated patients who did not develop LPD under MTX treatment (MTX non-LPD group) from those that did (MTX-LPD group), and conducted a comparative examination. We used multivariate analysis to determine the independent risk factors for MTX-LPD onset. Results: There were 33 patients in the MTX-LPD group and 145 patients in the MTX non-LPD group. The number of patients with DMARDs (except MTX) treatment showed no significant difference in two groups. Furthermore, there was no difference between two groups about that with corticosteroid and biologics treatment. Also, the complication rates for Sjögren's syndrome did not differ significantly. Using univariate analysis, significant differences were found in the duration of RA disease, Steinbrocker staging classification and mean MTX dose between the two groups. Multivariate analysis of the parameters extracted by univariate analysis revealed that the mean MTX dose was a risk factor for MTX-LPD after adjusting for age. Conclusions: We revealed the mean MTX dose was demonstrated to be an independent risk factor regarding MTX-LPD onset in RA patients. This data strongly suggest that the treatment with higher MTX dose promotes LPD onset in Japanese RA patients. References: Heldmann F, Braun J. Perioperative use of methotrexate. Clin Exp Rheumatol 2010; 28 (Suppl 61): S110–3. Ekström K, Hjalgrim H, Brandt L, Baecklund E, Klareskog L, Ekbom A, et al. Risk of malignant lymphomas in patients with rheumatoid arthritis and in their first-degree relatives. Arthritis Rheum 2003; 48: 963–70. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4752